2021
DOI: 10.1038/s41392-021-00718-w
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic landscape mapping of humoral immunity to SARS-CoV-2 identifies non-structural protein antibodies associated with the survival of critical COVID-19 patients

Abstract: A comprehensive analysis of the humoral immune response to the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is essential in understanding COVID-19 pathogenesis and developing antibody-based diagnostics and therapy. In this work, we performed a longitudinal analysis of antibody responses to SARS-CoV-2 proteins in 104 serum samples from 49 critical COVID-19 patients using a peptide-based SARS-CoV-2 proteome microarray. Our data show that the binding epitopes of IgM and IgG antibodies differ acros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 66 publications
2
33
0
Order By: Relevance
“…In a randomized phase 1/2 clinical trial with Valneva, antigen-specific interferon-γ T-cells reactive were observed against the spike, membrane, and nucleocapsid proteins [21]. Of course, take into account the fact that not all viral epitopes of the virus need to be immunogenic [23]. Research in this area is currently underway.…”
Section: Discussionmentioning
confidence: 99%
“…In a randomized phase 1/2 clinical trial with Valneva, antigen-specific interferon-γ T-cells reactive were observed against the spike, membrane, and nucleocapsid proteins [21]. Of course, take into account the fact that not all viral epitopes of the virus need to be immunogenic [23]. Research in this area is currently underway.…”
Section: Discussionmentioning
confidence: 99%
“…There was no corresponding neutralizing effect using antisera that recognized the C terminal region of SARS-CoV-1 ORF3a in two separate studies [61,62] after 2-4 days of infection. Previous studies have also revealed a significant proportion of convalescent sera or plasma of patients with ORF3a antibodies compared to patients who had succumbed to SARS-CoV infection [60,63]. This would support further exploration of the therapeutic potential of ORF3a antibodies.…”
Section: Discussionmentioning
confidence: 66%
“…In the recent studies about association between prognosis of COVID-19 and anti-SARS-CoV-2 antibody titer, non-structural protein targeted IgM antibodies were associated with a good prognosis and structural protein, including N protein, targeted IgG antibodies were associated with high mortality [ 22 ]. Although the kit we used measured structural protein targeted total antibodies including IgG, there was no significant difference in anti-SARS-CoV-2 antibody between patients who died and those who recovered from COVID-19.…”
Section: Discussionmentioning
confidence: 99%
“…good prognosis and structural protein, including N protein, targeted IgG antibodies were associated with high mortality [22]. Although the kit we used measured structural protein targeted total antibodies including IgG, there was no significant difference in anti-SARS-CoV-2 antibody between patients who died and those who recovered from COVID-19.…”
Section: Plos Onementioning
confidence: 95%